Scrum - Layton, Mark (Mark C.); Ostermiller, Steven J.; Kynaston, Dean J. (--For dummies., 2023)
Scrum—an organizing approach that exposes work progress and quality —is used all over the place in software development, but it’s not just for coders. Scrum For Dummies shows you how scrum can improve performance regardless of your industry or project. You can even use scrum to get tangible results in your personal projects—prepare for retirement, organize travel, and much more. Plan goals, releases, and sprints for all aspects of business and life. With Dummies, you’ll learn how to work flexibility and collaboration into anything you’re doing. This book is packed with helpful information to empower you to set up your first scrum project, organize the scrum team, integrate scrum into your agile project management strategy, and just make things work better. This updated edition of Scrum For Dummies is written to make scrum useful for everyone—especially you.